2014
DOI: 10.2337/db13-0752
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-Specific GLUT4-Deficient Mice Have Fewer and Larger Podocytes and Are Protected From Diabetic Nephropathy

Abstract: Podocytes are a major component of the glomerular filtration barrier, and their ability to sense insulin is essential to prevent proteinuria. Here we identify the insulin downstream effector GLUT4 as a key modulator of podocyte function in diabetic nephropathy (DN). Mice with a podocyte-specific deletion of GLUT4 (G4 KO) did not develop albuminuria despite having larger and fewer podocytes than wild-type (WT) mice. Glomeruli from G4 KO mice were protected from diabetes-induced hypertrophy, mesangial expansion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 55 publications
(88 reference statements)
1
51
0
Order By: Relevance
“…However, in brown adipocytes, insulin-mediated glucose transport and GLUT4 translocation are through IRS2, suggesting that podocytes and adipocytes display similar requirements of IRS2 in respect to insulin stimulated activation of AKT, GLUT4 translocation and glucose uptake [40]. Interestingly, it has recently been shown that there are insulin-independent roles of GLUT4 in podocytes that modulate their size and number [41], although it is unknown if these effects are modified by the IRS family. It is also clear that AKT2 has an important role in podocytes viability [30].…”
Section: Discussionmentioning
confidence: 97%
“…However, in brown adipocytes, insulin-mediated glucose transport and GLUT4 translocation are through IRS2, suggesting that podocytes and adipocytes display similar requirements of IRS2 in respect to insulin stimulated activation of AKT, GLUT4 translocation and glucose uptake [40]. Interestingly, it has recently been shown that there are insulin-independent roles of GLUT4 in podocytes that modulate their size and number [41], although it is unknown if these effects are modified by the IRS family. It is also clear that AKT2 has an important role in podocytes viability [30].…”
Section: Discussionmentioning
confidence: 97%
“…Insulin and muscle contraction are the major known mediators of GLUT4 translocation under physiological conditions [40,41]. The importance of podocyte insulin signaling in the pathogenesis of diabetic kidney disease is suggested by the observation that podocytes isolated from diabetic db/db mice cannot phosphorylate Akt in response to insulin and do not translocate GLUT4 to the plasma membrane after insulin stimulation [42]. We suggest that insulin induces the TRPC6-dependent entry of Ca 2+ into podocytes, the translocation of GLUT4 to the membrane, and, consequently, an increase in glucose uptake in podocytes.…”
Section: +mentioning
confidence: 99%
“…Patients with mutations in genes encoding different mitochondrial enzymes, such COQ2, COQ6, COQ10, and aarF domain-containing kinase 4 (ADCK4), present with podocyglomerulosclerosis, even in the absence of hyperglycemia (7). The effect of insulin receptor deletion appears to be independent of glucose uptake, as mice with podocyte-specific deletion of glucose transporter type 4 (Glut4) do not develop similar changes (8). Insulin-induced activation of AKT acts as an important regulator of cytoskeletal changes and prosurvival factor in podocytes and might explain the strong phenotype develop- The bigger picture…”
Section: Podocytes In Diabetesmentioning
confidence: 99%